2016
DOI: 10.4102/hsag.v21i0.964
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to facilitate professional development of the occupational health nurse in the occupational health setting

Abstract: Occupational health nurseOccupational health setting a b s t r a c t Background: Education and experience are important components in the ability of occupational health nurses (OHNs) to promote high-quality care and competence. OHNs will increasingly require the skills and knowledge to base care on best evidence, to use critical thinking and demonstrate advanced leadership and decision-making skills to develop and enhance services in a more complex and diverse occupational healthcare environment.Objective: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Occupational health is a diverse specialization of health care for improving the relationship between work and the physical and psychological health of employees [ 25 ]. Several studies have confirmed that job stress is a risk factor for adverse physiological function and psychological reaction [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Occupational health is a diverse specialization of health care for improving the relationship between work and the physical and psychological health of employees [ 25 ]. Several studies have confirmed that job stress is a risk factor for adverse physiological function and psychological reaction [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Psychosocial changes usually happen before physiological disorders are apparent, and there is often a lack of attention and intervention to address them [ 24 ]. Thus, the focus of occupational health management is not only on physical health, but also on mental health [ 25 ]. It is hence important to provide data on risk of stress and burnout for specific professional categories.…”
Section: Introductionmentioning
confidence: 99%